The prevalence of psychiatric symptoms of pregnant and non-pregnant women during the COVID-19 epidemic (2020)
Coronavirus disease 2019 (COVID-19) is rapidly spreading worldwide, with a staggering number of cases and deaths. However, available data on the psychological impacts of COVID-19 on pregnant women are limited. The purposes of this study were to assess the prevalence of psychiatric symptoms among pregnant women, and to compare them with non-pregnant women. From February 28 to March 12, 2020, a cross-sectional study of pregnant and nonpregnant women was performed in China. The online questionnaire was used to collect information of participants. The mental health status was assessed by patient health questionnaire, generalized anxiety disorder scale, insomnia severity index, somatization subscale of the symptom checklist 90, and post-traumatic stress disorder (PTSD) checklist5. Totally, 859 respondents were enrolled, including 544 pregnant women and 315 non-pregnant women. In this study, 5.3%, 6.8%, 2.4%, 2.6%, and 0.9% of pregnant women were identified to have symptoms of depression, anxiety, physical discomfort, insomnia, and PTSD, respectively. However, the corresponding prevalence rates among nonpregnant women were 17.5%, 17.5%, 2.5%, 5.4%, 5.7%, respectively. After adjusting for other covariates, we observed that pregnancy was associated a reduced risk of symptoms of depression (OR = 0.23; 95% CI: 0.12–0.45), anxiety (OR = 0.26; 95% CI: 0.16–0.42), insomnia (OR = 0.19; 95% CI: 0.06–0.58), and PTSD (OR = 0.15; 95% CI: 0.04–0.53) during the COVID-19 epidemic. Our results indicate that during the COVID-19 epidemic in China, pregnant women have an advantage of facing mental problems caused by COVID-19, showing fewer depression, anxiety, insomnia, and PTSD symptoms than non-pregnant women.